Statement made by Jane Tolmach to the Members of the Airport Authority August, 1999 - Jane Tolmach:::::: (1999)
A statement made by Jane Tolmach requesting the members of the Airport Authority to provide the Draft Revised Oxnard Airport Master Plan, the Environmental Impact Report, to search for a new Director, and information about the cost of buying out the FAA's investment in the Oxnard Airport.